Spatial thinking of the present pathogenic complexes: comparative analysis of Dengue Fever and American Cutaneous Leishmaniasis - Guimaraes, Raul Borges [UNESP]; Catao, Rafael de Castro; Casagrande, Baltazar [UNESP] (Revues Org, 2018)
In the present article we aim to thought about the Geography of Health's Epistemological Status, systematized with the basis of the discipline classical authors while a specific mode to think present dengue fever's and American Cutaneous Leishmaniosis' pathogenic complexes. Sorre proposed the pathogenic complex in 1930s, within the French Geography School, to comprehend the diseases in geographical space. This theory was developed in an expansion phase of urban-industrial society, and keeps aspects of this phase. We propose a rereading of this concept, by the introduction of the spatial thinking in the infectious-parasitic analysis that are persistent in the present, contemporaneous links of the technical-scientific and information's period, as well, the comprehension of the coexistence of geographical milieus with distinguish technical, scientific and informational contents, modulating the interaction between the elements of the complex. We will exemplify the rereading with the comparative analysis of two pathogenic complexes (Dengue Fever and American Cutaneous Leishmaniosis) in Sao Paulo State (Brazil), which have distinguished epidemiologic cycles and predominance in different geographical milieus, emphasizing the geographical aspect that supports the pathogenic complex.
Keywords: Pathogenic Complex; Spatial Thinking; Dengue Fever; American Cutaneous Leishmaniosis; Sao Paulo State